1999
DOI: 10.1001/archotol.125.5.530
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Pediatric Tympanoplasty

Abstract: Greater success in healing of the tympanic membrane following tympanoplasty in children is seen with advancing age. None of the other parameters studied was shown to be a significant predictor of success. Guidelines for reporting results of tympanoplasty are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
1
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(164 citation statements)
references
References 23 publications
9
146
1
8
Order By: Relevance
“…Salviz et al [29] reported that presence of adenoid hypertrophy was associated with low success rates. We did not find any statistically significant difference between patients who had or had not undergone previous adenoidectomy, a result that agrees with those published by most authors [5,9,15]. Ribeiro et al [7] reported that a previous adenoidectomy in patients older than 10 years seem to be an independent predictor of functional success.…”
Section: Role Of Adenoidecomysupporting
confidence: 91%
See 2 more Smart Citations
“…Salviz et al [29] reported that presence of adenoid hypertrophy was associated with low success rates. We did not find any statistically significant difference between patients who had or had not undergone previous adenoidectomy, a result that agrees with those published by most authors [5,9,15]. Ribeiro et al [7] reported that a previous adenoidectomy in patients older than 10 years seem to be an independent predictor of functional success.…”
Section: Role Of Adenoidecomysupporting
confidence: 91%
“…Rozendorn et al [19] reported that age under 9 years is associated with significantly higher rates of persistant and recurrent perforations. Vrabec et al [5] found better success rate with advancing age. Pignataro et al [9] and Denoyelle et al [16] had reported no significant correlation between age and surgical outcome.…”
Section: Patient Agementioning
confidence: 94%
See 1 more Smart Citation
“…However, some researchers have suggested that tympanoplasty should be postponed until the age of 7, 10, 11, and 12 years in children [18][19][20][21] . Vrabec et al [22] performed a meta-analysis of 30 studies including a 30-year period and reported age-specific data. They concluded that age contributed to postoperative successful recovery rates and that other parameters did not have any significant relationships with a good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis done by Vrabec et al 17 considering the effect of otorrhea on closure rate indicates that tympanoplasty on a discharging ear is as successful as in a dry ear.…”
Section: 6-15mentioning
confidence: 99%